ANALYSIS OF WELDING DEFECTS AND BENDING STRENGTH IN ASTM A36 STEEL MATERIALS E7018 ELECTRODES - Fredderik Yodianto (POLITEKNIK NEGERI BENGKALIS, 2023)
This study aims to determine the effect of variations in current strength and groove type in SMAW welding on defects in welds and bending strength of ASTM A36 steel butt joint. In this study, the sample used was ASTM A36 steel with welding variations of current strength, namely 90 A, 110 A, and 130 A as well as variations in the form of V and Single V groove with SMAW welding using E7018 electrodes. Specimens were tested for NDT in the form of a visual test, penetrant test, and magnetic test, and DT Testing in the form of a bending test. In the NDT test, defects were found in the 90 A current specimen in the form of spatter defects, arc strike. At a current of 110 A, there are spatter, undercut, and porosity defects. At a current of 130 A, there are spatter, undercut, and overlap defects. The highest bending strength DT test results were in the SV and V groove with a current of 90 A and the lowest value was in the V groove with a current of 110 A of 1069.44 Mpa. After the NDT test, current variations have an influence on the results of the weld, but it cannot be ascertained that the effect on the groove type, while in the DT test, current variations and groove types have an effect on bending strength.